Analisis Profitabilitas, Likuiditas, Leverage dan Ukuran Perusahaan terhadap Pertumbuhan Laba - Rinny Meidiyustiani; Retno Fuji Oktaviani; Hakam Ali Niazi (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2021)
The purpose of this study is to test and analyze empirically the effect of profitability, liquidity, leverage and firm size on profit growth. This study uses secondary data, the population used by manufacturing companies in the consumer goods industry sector listed on the Indonesian Stock Exchange for the period 2014 – 2018 was 32 companies. The sample used was taken by purposive sampling method. Multiple Linear Regression is used to assist the analysis in this study. The results of this study partially show that there is a significant effect of profitability in a positive direction on profit growth. As for liquidity, leverage, and company size partially do not have a significant effect on profit growth.